Are Parental Stress and Rewards Influenced by Child Temperament? Analysis of the Moderating Role of Social Support and Gender in Spanish Parents - Olga Gómez-Ortiz; María Ortiz-Alba; Daniel Falla; Eva M. Romera (Psychosocial Intervention)

(untitled)
Objective: The aims of this research work were twofold: (1) to validate the factor structure of the Spanish version of the Emotionality, Activity and Sociability Temperament Survey (EAS) and (2) to analyse the relationship between child temperament, and parental stress and rewards, testing the possible moderating roles of gender and social support. Method: The reference population was a group of mothers and fathers with children in early childhood education (aged 0-5). For the first study, we used a sample of 701 subjects (70.20% mothers, Mage = 36.83), while for the second study, 422 individuals were selected (58.9% mothers, Mage = 37.08). We conducted exploratory (EFA) and confirmatory factor analyses (CFA) and moderation analyses. Results: The EFA showed a three-factor structure composed of 12 items, and the CFA verified that the three-factor model (sociability, emotionality, and activity) was the most parsimonious and provided the best fit. The results reveal the moderating effect of social support and gender in the relationship between childhood emotionality and parental rewards. One the one hand, with mothers in particular, the parental rewards are especially affected by childhood emotionality when levels of social support are low to moderate. On the other hand, paternal rewards seem to depend to a greater extent on childhood emotionality when there is a high level of support from a significant other. Conclusions: Finally, we discuss the protective role played by social support and the possible risk factor of childhood emotionality in parents’ appraisal of the parenting task, depending on the gender of the parents.